Protecting the pawners: appraising the role of Ministry of Urban Wellbeing, Housing and Local Government - Kassim, Salina; Hassan, Rusni; Abu Bakar, Elistina; Ilias, Ibtisam @ Ilyana (2018)
The role of consumer credit in modern society is vital particularly when poor economic conditions prevail and cost of living soars. In view of the difficulties to access credit, low and middle-income earners commonly pledge their valuables in exchange for cash by resorting to pawnshops which are often labeled as a bank for poor. In this context, the role of the regulator is highly critical and indispensable since the poor being on the disadvantage side of having low bargaining power. This study examines the role of the Ministry of Housing and Local Government in Malaysia which has been mandated to safeguard the interest of pawners under conventional pawnbroking in Malaysia. The scope of discussion covers its institutional set-up, organisational structure while regulatory powers concentrate on licensing and enforcement based on the relevant statutory provisions. Several shortcomings are identified in respect of licensing requirements, enforcement powers and human resources. The study finds that entrusting this Ministry with consumer protection function is inappropriate, thus several recommendations to enhance protection for this class of consumer are proposed.